Characterization of Biological Parts for Modular Genetic Devices: A Comparative Analysis (International Journal of Innovative Computing, 2016)
Synthetic biology is a new field that attempting to catalyze new approaches in biotechnology, medicine and other scientific research for engineer biological systems. The area focuses on designing modular and robust genetic devices to facilitate their reuse and reliability in different context. Biological parts are characterized according to their suitable joining to create genetic devices. These biological parts and devices are represented in form of electronic gates. In this paper, we reviewed existing method in designing biological parts and genetic devices in order to build complex system biology. We also highlighted a research to help researchers for expecting forthcoming trends in this area